2017
DOI: 10.1177/1087054717723987
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Training for Adults With ADHD

Abstract: The results challenge the claims made by Cogmed to the effect that the program is effective in treating attention problems and improving performance in daily life over the long term in adults with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
1
18
0
1
Order By: Relevance
“…However, given that CPT performance is generally stable and test–retest effects are rarely observed (Halperin et al, 1991), these improvements might still be of clinical value, especially since the participants with ADHD did no longer differ from the healthy controls at post‐test (see commission errors at Table S4). The limited effects of WM training on ADHD symptoms in adults are also in line with previous work (Dentz, Guay, Parent, & Romo, 2017). Curiously, self‐reported ADHD symptoms decreased relative to the Active control group only in those participants who improved the least in the trained task.…”
Section: Discussionsupporting
confidence: 90%
“…However, given that CPT performance is generally stable and test–retest effects are rarely observed (Halperin et al, 1991), these improvements might still be of clinical value, especially since the participants with ADHD did no longer differ from the healthy controls at post‐test (see commission errors at Table S4). The limited effects of WM training on ADHD symptoms in adults are also in line with previous work (Dentz, Guay, Parent, & Romo, 2017). Curiously, self‐reported ADHD symptoms decreased relative to the Active control group only in those participants who improved the least in the trained task.…”
Section: Discussionsupporting
confidence: 90%
“…Six RCT studies were conducted after these three meta-analyses were published. While five studies reported improvement in the working memory domain of the group that had received CR ( 111 115 ), Bigorra et al ( 116 ) reported no significant change in their study. Only Bigorra et al ( 114 ) reported improvement in ADHD symptoms, while the other five RCT studies did not investigate or report significant change in ADHD symptoms and academic skills ( 111 113 , 115 , 116 ).…”
Section: Current Status Of Cognitive Remediation Trialsmentioning
confidence: 91%
“…While no systematic review examining CWMT attrition in comparable populations exists, we did find a number of studies that provided insights. In particular, three research groups ( 25 , 26 , 32 ) have specifically examined the suitability and efficacy of CWMT for adults with ADHD. Mawjee and colleagues aimed to compare standard-length (45 min-the duration used in our study) and shortened-length (15 min) CWMT.…”
Section: Intolerability Of Cwmt In Adults With Adhdmentioning
confidence: 99%
“…Two recent studies provide somewhat more optimistic estimates of tolerability. First, Dentz et al ( 25 ) investigated the efficacy of CWMT in ADHD-diagnosed adults recruited through a mental health clinic. However, the earlier study Cogmed coaching in this study was performed by a research assistant rather than a clinician.…”
Section: Intolerability Of Cwmt In Adults With Adhdmentioning
confidence: 99%